2016
DOI: 10.1017/s1049023x16001163
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Application of a Triage Sieve: A Paper-Based Exercise

Abstract: This study supports the use of an aide-memoir for maximizing MCI triage accuracy rates. A "just-in-time" educational refresher provided comparable benefits, however its practical application to the MCI setting has significant operational limitations. In addition, this study provides some guidance on triage sieve accuracy rate measures that can be applied to define acceptable performance of a triage sieve during a MCI. Cuttance G , Dansie K , Rayner T . Paramedic application of a triage sieve: a paper-based exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…However, two participants were upwards relieving into the role and were excluded, having taken part in the previous study as paramedics; 17 data sets were obtained from this sample population. (15), Table 2 shows that the level of underlying triage sieve training was identical between the two groups, although team leaders were more likely to have performed a triage sieve as part of an exercise or in real life. Similarly, team leaders were more likely to know the correct location of the triage pack.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, two participants were upwards relieving into the role and were excluded, having taken part in the previous study as paramedics; 17 data sets were obtained from this sample population. (15), Table 2 shows that the level of underlying triage sieve training was identical between the two groups, although team leaders were more likely to have performed a triage sieve as part of an exercise or in real life. Similarly, team leaders were more likely to know the correct location of the triage pack.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the current field triage accuracy rates for MCI triage may be inappropriate (23) and overstated for MCI triage. Cuttance et al (15) have shown that it is possible to achieve under-and over-triage rates of 2.8% and 7.0% respectively using supportive documentation. Achievement of the aforementioned triage accuracy rates was dependant on the use of supportive documentation (aide-memoir) with the ability to correctly locate the triage pack imperative, as the triage pack contains the most up-todate triage sieve aide-memoir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations